The Mediating Effect Of Online Buying Behavior In Relationship Between The Antecedents Of Consumer Behavior And Customer Retention And Loyalty (Journal of Namibian Studies : History Politics Culture, 2023)
Aim/purpose:-The aim of the descriptive research study was to investigate and understand the mediating effect of online buying behavior in relationship between the antecedents of consumer behavior and customer retention and loyalty. The study seeks to examine how positively online experiences contribute to customer retention and loyalty which facilitates to maintain long-term customer relationship.Outcome:- The outcome of the research study uncover the key antecedents of consumer behavior in online context and the mediating role of online buying behavior  between antecedents and customer retention/loyalty. Further, the outcome of the research will provide recommendations for marketers and businesses to develop strategies for positive online experience, fostering customer loyalty and retention in the competitive market.Research Design/Methodology/Approach:- The study adopt a descriptive research design by utilizing both quantitative and qualitative data. The convenience sampling strategy employed to select respondents who have recent online buying experience.Statistical tools:- Researcher applied both descriptive and inferential statistical tools. The statistical tools like: correlation, regression and structural equation modeling (SEM) applied. The model has shown the accuracy of 94% all the GFI, AGFI, NFI, CFI and TLI values are >.90 and RMSEA